Bidirectional association between breast cancer and dementia: a systematic review and meta-analysis of observational studies - Fuxing Bao; Liang Yu; Xiaolei Zhang; Qier Mu (PeerJ)
Background Cognitive decline following cancer treatment can vary from mild cognitive impairment to severe dementia. However, there is inconsistent evidence regarding the relationship between breast cancer survivors and their risk of developing dementia. This meta-analysis aims to consolidate observational studies to explore the bidirectional association between breast cancer and dementia risk. Methods We conducted a comprehensive search using medical subject headings (MeSH) and keywords across PubMed, Cochrane Library, and Embase databases to identify cohort, case-control, and cross-sectional studies examining the link between breast cancer and dementia risk. Statistical analysis was performed using Stata version 14.0, with a random effects model employed to account for heterogeneity. Publication bias was assessed using funnel plots and Egger’s test. Results This meta-analysis included 13 studies with a total of 346,051 participants, up to June 20, 2024. Of these, seven studies investigated the risk of dementia among patients with breast cancer, revealing a lower risk [OR = 0.56, 95% CI [0.27–1.18], I2 = 99.1%, P = 0.128]. Similarly, seven studies explored the risk of breast cancer in individuals with dementia, showing a lower risk as well [OR = 0.79, 95% CI [0.51–1.22], I2 = 94.5%, P = 0.290]. Conclusion Our findings indicate that breast cancer is less likely to lead to dementia and that dementia is similarly low associated with risk of breast cancer. These insights are crucial for clinicians in guiding the prevention and monitoring of neurodegenerative conditions in patients with breast cancer.